2002
DOI: 10.3354/meps245171
|View full text |Cite
|
Sign up to set email alerts
|

Grazing pressure by amphipods on microalgae in Gamo Lagoon, Japan

Abstract: Grazing effects of amphipods were examined for 3 groups of diatoms (loosely attached cells, moderately attached cells and strongly attached cells) in Gamo Lagoon, Miyagi Prefecture, Japan. Diatom species with filamentous forms or low adhesive strength were susceptible to grazing, while those with stronger adhesion were less affected by grazing pressure. Seasonal trends for both amphipods and microalgae found on the macroalgae Gracilaria vermiculophylla showed high densities of amphipods and low densities of mi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

2006
2006
2024
2024

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 24 publications
(8 citation statements)
references
References 23 publications
0
8
0
Order By: Relevance
“…A previous study reported that the population dynamics of the amphipod Corophium volutator are controlled by water temperature in the summer (Wilson and Parker 1996). Furthermore, Aikins and Kikuchi (2002) found that the population density of C. uenoi and G. japonica at our study site was closely correlated with the macroalgal biomass used as a substrate for constructing their tubes. Further study is needed to clarify the potential factors controlling amphipod population dynamics.…”
Section: Sediment Typesmentioning
confidence: 87%
“…A previous study reported that the population dynamics of the amphipod Corophium volutator are controlled by water temperature in the summer (Wilson and Parker 1996). Furthermore, Aikins and Kikuchi (2002) found that the population density of C. uenoi and G. japonica at our study site was closely correlated with the macroalgal biomass used as a substrate for constructing their tubes. Further study is needed to clarify the potential factors controlling amphipod population dynamics.…”
Section: Sediment Typesmentioning
confidence: 87%
“…Their densities were quite comparable to those found in the brackish waters of France (1300 ind.m −2 (Lavesque et al 2014)) and British isles (1500-5800 ind m −2 (Smith et al 1999)). As the availability of food such as algae seems to have an important role on its reproduction (Aikins and Kikuchi 2002), we hypothesize that G. japonica have found a suitable habitat in the Sacca di Goro. The finding of ovigerous females from samples collected in the Sacca di Goro in summer 2015 seems to support our hypothesis.…”
Section: Discussionmentioning
confidence: 99%
“…No chemical or structural defenses known from benthic species. This genus is a common item in the diet of some estuarine fishes (Almeida, 2003), but it is likely grazed upon more commonly by smaller invertebrates such as crustaceans and snails (AuriolesGamboa and PerezFlores, 1997;Jensen and Asplen, 1998;Sommer, 1999;Aikins and Kikuchi, 2002) 2 Shimizu et al (1982) Microdictyon Finely branched ''cushion-like'' green algae with a crisp and fragile thallus (Littler and Littler, 2000). No data are available on palatability 9 Shimizu et al (1982), Gillespie et al (1985a) Padina Lightly to moderately calcified (Wefer, 1980;Okazaki et al, 1986;Kerkar, 1994;Payri, 1995) fan-shaped brown algal genus, with some species also producing halogenated terpenes (Parameswaran et al, 1994) and polyphenolics (Karez and Pereira, 1995).…”
Section: Bourdeau and Durand-clement (1991) Lyngbyamentioning
confidence: 98%